Risk of failure in dual therapy versus triple therapy in naïve HIV patients: a systematic review and meta-analysis. (January 2021) - Pisaturo, Mariantonietta; Onorato, Lorenzo; Russo, Antonio; Martini, Salvatore; Chiodini, Paolo; Signoriello, Simona; Maggi, Paolo; Coppola, Nicola
Abstract: Objectives: Several attempts have been made to test different drug-sparing strategies to reduce the drug-burden and drug-related toxicities. The objective of this meta-analysis was to evaluate the relative risk (RR) of failure of dual therapies compared to triple therapies in HIV-naïve patients. Methods: We searched MEDLINE, Google Scholar and the Cochrane Library. The following criteria were used: present data from original articles comparing the two treatment regimens; published from January 2007 up to January, 2020. No language or study design restriction was applied. Subjects were HIV-positive naïve patients treated with dual or triple antiretroviral therapy (ART). A systematic review and meta-analysis was performed. Treatment failure (TF) was the primary outcome evaluated; heterogeneity was assessed using the Q statistic and I 2 . Results: Fourteen studies were included, allowing a meta-analysis on 5205 patients. The meta-analysis performed on studies that presented data at 48 weeks showed that the RR of TF (RR > 1 favouring triple therapy) in 10 studies was 1.20 (95% confidence interval (CI): 0.91–1.59, I 2 : 49.2%); the RR of virological failure (VF) in eight studies was 1.54 (95% CI: 0.84–2.86, I 2 : 54%); the RR of adverse drug reaction leading to discontinuation of the regimen at 48 weeks in eight studies was 0.76 (95% CI: 0.43–1.33, I 2 : 17.7%). In patients with less than 200 CD4+, the RR of TF in two studies without maraviroc was 2.09 (95% CI: 1.05–4.17, I 2 : 0.0%). Regarding the studies at 96 weeks there was no difference except in rate of development of resistance, RR 1.94 (95% CI: 1.06–3.53, I 2 : 6.2%). Conclusion: Dual therapies are as effective as those with three drugs, showing no difference according to the different dual therapies, except in patients with less than 200 CD4; however, they are associated with a higher selection of resistance-associated mutations at 96 weeks of therapy.